Isotonic Drink Formulation Based on Coconut Water and Starfruit Juice with a Sweetening Combination of Sucrose, Stevia, and Honey - Taneasy, Ian; Dewi, Yohana Sutiknyawati Kusuma; Lestari, Oke Anandika (FoodTech: Jurnal Teknologi Pangan, 2025)
An isotonic drink is a formulation drink intended to rapidly replace liquids, carbohydrates, electrolytes and body minerals, so that it can be absorbed by the body after drinking. This study aims to find the types of sweetening formulations of sucrose, stevia and honey that produce the best physiochemical and sensory characteristics of coconut water isotonic drink lead. This research design uses a Group Randomization Plan (RAK) with 1 factor, namely variations in sweetener formulations (sucrose: honey: stevia) with a repeat count of 5 experimental units, resulting in a total of 25 samples consisting of 5 treatment standards. The observation results data were processed using Analysis of Variants (ANOVA). Determination of the best treatment using the efficacy index test. Physicochemical and sensory characteristics of coconut water isotonic drinks and from the best lead-twentieth are found in the formulation f2 having a treatment value (NP) of 0.61 with a pH of 3.07, a TPT value of 5.32 °Brix, a sodium content of 903.06 mg/kg, a level of 419.8 mg/kg, antioxidant activity of 20.81%, and a total acid value of 0.165%, respectively. It is also used in organoleptic testing with a 3.37 aroma, 3.97 flavor and a 3.77 overall favorite.